2002
DOI: 10.1046/j.1525-1497.2002.10603.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ use of the internet for medical information

Abstract: Primary care providers should recognize that patients are using the World Wide Web as a source of medical and health information and should be prepared to offer suggestions for Web-based health resources and to assist patients in evaluating the quality of medical information available on the Internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
584
5
27

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 848 publications
(637 citation statements)
references
References 20 publications
21
584
5
27
Order By: Relevance
“…Quality is a major issue in consumer health information available on World Wide Web as found in a systemic review [3]. Another study estimated that more than half of the patients use Internet for advice on health issues without discussing it with their physicians [4]. This behaviour has been found more prevalent in younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…Quality is a major issue in consumer health information available on World Wide Web as found in a systemic review [3]. Another study estimated that more than half of the patients use Internet for advice on health issues without discussing it with their physicians [4]. This behaviour has been found more prevalent in younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…41% of health seekers who got Internet information prior to a visit discussed this information with their doctors, and those that did rated the quality of the information higher (Diaz et al, 2002). The August 2002 survey (Fox & Rainie, 2002a) indicated that while only 9% have communicated online with a doctor, 61% of those who sought health information for themselves looked for Web resources in connection with a visit to the doctor.…”
Section: Online Health Information As a Source For Support And Interamentioning
confidence: 99%
“…This is already common in North America. 4,5 However, while there is a considerable body of research on the impact of the Internet as it relates to medicine in general, 6 there is little evidence about how the Internet is impacting on dentistry in the UK. 7 The first study of dental information for patients on the Internet concluded that judicious and active support from professionals would be required to aid patients' interpretation of periodontal-related patient information sites.…”
Section: Introductionmentioning
confidence: 99%